Integration of Qualitative Approaches in Research in Counseling - Abdillah Muhammad Zaini; Anggi Melviyanti; Dara Agustina; Delia Putri Utami; Juliana Sari; Juriani Harahap; May Purnama Sari; Putri Syahri (PT Inovasi Pratama Internasional, 2023)
This study aims to determine the integration of research with a qualitative approach in the field of counseling as well as to describe and discuss the nature of the qualitative research method, its characteristics and position in the field of counseling. The qualitative research methods in the field of counseling include descriptions of counseling in Indonesia, other forms of qualitative research in counseling, collecting data from qualitative research in the field of counseling and qualitative research steps in the field of counseling in accordance with data obtained in the field. A qualitative approach is suitable for use in counseling research because it contains a wide range of research according to needs.